Myristylation of Rous sarcoma virus Gag protein does not prevent replication in avian cells. - Erdie, C R (1990)
Rous sarcoma virus is an example of a replication-competent retrovirus whose Gag protein is not modified with myristic acid. The purpose of the experiments described in this report was to determine whether the addition of this 14-carbon fatty acid would interfere with the replication of Rous sarcoma virus. We found that myristylated derivatives of the Rous sarcoma virus Gag protein are fully functional for particle formation in avian cells and that the addition of myristic acid has very little effect on infectivity.